A diagnostic, test-accuracy study to evaluate the ability of the Eye Guide Visual Tracking System and the Post-Concussion Symptom Scale to diagnose mild TBI and predict protracted recovery. Issue 4 (11th October 2022) - Fernandez, Laura Lucia; Griswold, Dylan P; Fariyike, Bunmi; Aristizabal, Sarita; Perez, Brian; Rubiano, Andres M
Abstract: Mild traumatic brain injury (mTBI) is the most common type of traumatic brain injury (TBI), and 100–300 individuals per every 100 000 seek medical care for mTBI annually. The Eye Guide is a portable device that evaluates oculomotor function. This device has promising potential to detect trauma-related neurological deficits that are otherwise undetected by a non-contrast computed tomography scan, the current gold standard. However, to our knowledge, a study has yet to be conducted that evaluates its ability to detect mTBIs specifically. By contrast, the Post-Concussion Symptom Scale (PCSS) is a 22-item, self-reported symptom survey that has become one of the most trusted tools in evaluating mTBI-related sequelae. Although this scale has been well validated in adolescent athletes, there is a notable lack of studies defining its clinical utility in adults with non-sports-related trauma. Patients with mTBI are expected to have detectable alterations in the PCSS score and the Eye Guide visual tracing. Thus, this study aims to determine each tool's diagnostic accuracy in detecting mTBI and prognostic accuracy in predicting a protracted recovery in our patient population. Additionally, for both tools, we seek to establish cut-off values for future clinical decision-making in non-athlete, adult populations. A prospective, observational cohort test-accuracy study will be conducted in two clinics that form part of the ValleSalud Clinic Network in Cali, Colombia. Both are Level III referral trauma centers. The sensitivity, specificity and positive predictive value of both the Eye Guide and PCSS tests in diagnosing mTBI and predicting protracted recovery will serve as primary outcomes of the study. Additionally, the area under the curve analyses will be undertaken to determine the optimal sensitivity and specificity cut-offs for each test. The ground truth labels will be the diagnosis of mTBI by neurological examination as evaluated by an experienced neurosurgeon and recovery at 1 month post-injury according to the Extended Glasgow Outcome Scale. This study will follow the principles set forth by the Declaration of Helsinki.